Caste artifical and natural - Stone, H. W. (My University, 1892)
Introduction: To state with the anarchist that there should be no classes in society is to ignore all natural laws. Yet any thinking observer must perceive that the fixed castes of India and China produce a stationary civilizations; and in Europe, where caste is less absolute progress in slowest where class distinction are most rigidly drawn, which the opposite proves equally true, that where there is most freedom from caste there is the greatest advancement. This is easily perceived by noting the two extremes of Russia with her serf and absolute monarch, the one as hopelessly doomed to his fate by his birth as the other, and England a limited monarchy where the humblest yeoman may become Prime Minister. Are we to conclude then that there should be no class distinction? Would the socialistic idea solve the questions? Would political enactment make men equal? Or is there not back of all this a natural law which, if obeyed, would harmoniously manage social conditions; and which, if violated prevents men from attaining unto their fullest capabilities?
Citation: Stone, H. W. Caste artifical and natural. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Caste; Social; Monarchy; Artificial; Sociology; Theses; Manuscripts (documents)